203k views
2 votes
Find the value

Bsisheghdhhdhcjfjfhfhdh

Find the value Bsisheghdhhdhcjfjfhfhdh-example-1

1 Answer

7 votes

For this case we have the following expression:


3 + 2 \sqrt {2} + \frac {1} {3 + 2 \sqrt {2}} =

We rationalize the second term multiplying by:


\frac {3-2 \sqrt {2}} {3-2 \sqrt {2}}:
\frac {1} {3 + 2 \sqrt {2}} * \frac {3-2 \sqrt {2}} {3-2 \sqrt {2}} = \frac {3-2 \sqrt {2} } {9-6 \sqrt {2} +6 \sqrt {2} -4 (\sqrt {2}) ^ 2} = \frac {3-2 \sqrt {2}} {9-4 * 2} = \frac {3-2 \sqrt {2}} {1} = 3-2 \sqrt {2}

So, we have:


3 + 2 \sqrt {2} + 3-2 \sqrt {2} = 3 + 3 = 6

Answer:

6

User Akshay Rao
by
4.6k points